2011
DOI: 10.1042/bj20110025
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine 5′-phosphosulfate reductase (APR2) mutation inArabidopsisimplicates glutathione deficiency in selenate toxicity

Abstract: APR2 is the dominant APR (adenosine 5'-phosphosulfate reductase) in the model plant Arabidopsis thaliana, and converts activated sulfate to sulfite, a key reaction in the sulfate reduction pathway. To determine whether APR2 has a role in selenium tolerance and metabolism, a mutant Arabidopsis line (apr2-1) was studied. apr2-1 plants had decreased selenate tolerance and photosynthetic efficiency. Sulfur metabolism was perturbed in apr2-1 plants grown on selenate, as observed by an increase in total sulfur and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 56 publications
2
50
0
1
Order By: Relevance
“…Se (in the forms of sodium selenate and sodium selenite) has two opposing effects on lettuce plant metabolism: at low doses it acts as an antioxidant and enhances plant growth, whereas at higher levels it reduces yields [26]. Selenium toxicity in high doses was also confirmed by other authors [49,50].…”
Section: Resultssupporting
confidence: 70%
“…Se (in the forms of sodium selenate and sodium selenite) has two opposing effects on lettuce plant metabolism: at low doses it acts as an antioxidant and enhances plant growth, whereas at higher levels it reduces yields [26]. Selenium toxicity in high doses was also confirmed by other authors [49,50].…”
Section: Resultssupporting
confidence: 70%
“…Generally, under Se stress decreased level of glutathione is observed (Hugouvieux et al, 2009), except in Se-tolerant plants where elevated levels are observed (Grant et al, 2011). In another study by Grant et al (2011) on cad2-1 mutant plants having defective glutathione synthetic pathway showed many folds decreased root length as compared to wild type plants grown on 20 μM selenate. In apr2-1 mutant of Arabidopsis , glutathione depletion and ROS accumulation found to be interlinked to each other under Se stress (Grant et al, 2011).…”
Section: Selenium Toxicity In Plantsmentioning
confidence: 99%
“…For example, APR2 regulates both the assimilation of sulfur (Loudet et al, 2007) and selenium (Grant et al, 2011;Chao et al, 2014) in Arabidopsis. Intriguingly, apr2-1 mutants had decreased Se in protein, but were still Se sensitive due to the accumulation of selenate that caused an accumulation of superoxide.…”
Section: Responsementioning
confidence: 99%